Convergence of interests in educational reform in Latin America and the Caribbean: genealogy and enactment of a multilevel governance network (Práxis Educativa, 2024)
This article aims to understand the emergence and action of a multilevel governance network in Latin America and the Caribbean. To this end, the Latin American Network of Civil Society Organizations for Education (REDUCA) is analyzed, a “network of networks” that seeks to promote a regional agenda in line with global education reform, without neglecting the interests of locally organized entrepreneurs. Drawing from theoretical frameworks by Rhodes (2007) and Jessop (1998) on new governance and employing methods such as document analysis, event observation and interviews, the connection between the origin of REDUCA and the context, actors, and objectives of the networks that preceded it from a relational perspective is established. The study highlights how the dynamics between the local, regional, and global levels can be impacted by the convergence of interests between multilateral organizations and business networks and raises questions about the relationship between multilevel governance and democratic participation.Keywords: Educational reform. Multilevel governance of education. Policy networks. Latin America and Caribbean. REDUCA.